2021
DOI: 10.1002/biof.1720
|View full text |Cite
|
Sign up to set email alerts
|

Analytical determinations of luteolin

Abstract: Plants, through the photosynthesis process, produce the substances necessary for all the life cycles of nature, which are called "primary metabolites." Moreover, there are some plants that synthesize, in addition to these, other substances with more specific functions, which are known as "secondary metabolites." It is inside this group that flavonoids are located, whose main function is to protect organisms from damage caused by different oxidizing agents. Luteolin (3,4,5,7-tetrahydroxy-flavone) belongs to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Luteolin (3’,4’,5,7-tetrahydroxy-flavone) is a compound belonging to the flavonoid subclass and is considered one of the most bioactive polyphenols [ 135 ]. This glycosylated flavonoid is present in fruit and vegetables, particularly oranges, carrots, celery, broccoli, parsley, and chamomile [ 136 ].…”
Section: Molecular Mechanisms Of Polyphenol Action On Neuroinflammati...mentioning
confidence: 99%
“…Luteolin (3’,4’,5,7-tetrahydroxy-flavone) is a compound belonging to the flavonoid subclass and is considered one of the most bioactive polyphenols [ 135 ]. This glycosylated flavonoid is present in fruit and vegetables, particularly oranges, carrots, celery, broccoli, parsley, and chamomile [ 136 ].…”
Section: Molecular Mechanisms Of Polyphenol Action On Neuroinflammati...mentioning
confidence: 99%
“…As one of the most bioactive flavonoids, luteolin (LUT) is a kind of natural ingredient extracted from a variety of medicinal plants, fruits and vegetables, such as Lonicera japonica Thunb. (Caprifoliaceae) (Tesio and Robledo, 2021). Recently, the increasing reduction in the application of synthetic antioxidants makes the study of LUT a very active field.…”
Section: Luteolinmentioning
confidence: 99%
“…Luteolin (3′,4′,5,7-tetrahydroxy flavone), a dietary flavone, is found in different plants and has a C6-C3-C6 structure containing two benzene rings and one oxygencontaining ring with a C2-C3 carbon double bond [14,15]. It has been reported that luteolin could diminish infarct size and neutrophil accumulation in the ischemic myocardium [12,16,17].…”
Section: Introductionmentioning
confidence: 99%